2006
DOI: 10.1242/jeb.02310
|View full text |Cite
|
Sign up to set email alerts
|

The cost of running uphill: linking organismal and muscle energy use in guinea fowl (Numida meleagris)

Abstract: SUMMARY Uphill running requires more energy than level running at the same speed,largely due to the additional mechanical work of elevating the body weight. We explored the distribution of energy use among the leg muscles of guinea fowl running on the level and uphill using both organismal energy expenditure(oxygen consumption) and muscle blood flow measurements. We tested each bird under four conditions: (1) rest, (2) a moderate-speed level run at 1.5 m s–1, (3) an incline run at 1.5 m s–1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…On balance it seems probable that positive work per stride increases above the value in level running when the birds run uphill. This conclusion is consistent with the substantial increase in energy use by the ILPO during uphill running (Rubenson et al, 2006).…”
Section: When Running Uphill the Ilpo Increases Active Shortening Ansupporting
confidence: 87%
See 4 more Smart Citations
“…On balance it seems probable that positive work per stride increases above the value in level running when the birds run uphill. This conclusion is consistent with the substantial increase in energy use by the ILPO during uphill running (Rubenson et al, 2006).…”
Section: When Running Uphill the Ilpo Increases Active Shortening Ansupporting
confidence: 87%
“…Estimates of energy use by the ILPO are based on the rate of blood flow to the muscle during activity (Ellerby et al, 2005;Ellerby and Marsh, 2006;Rubenson et al, 2006). Marsh and Ellerby reviewed the use of muscle blood flow as an indicator of muscle energy use and concluded that for aerobically supported exercise the data from human and animal studies support a linear and proportional relationship between blood flow and energy use .…”
Section: Matching Blood Flow Data From the Literature To Emg Datamentioning
confidence: 99%
See 3 more Smart Citations